Nivel de aprendizaje significativo en docentes de educación inicial Institución Educativa los Árbolitos y 602 Primavera, Iquitos 2021 - Ramirez Palomino, Sharon Denisse (2024)
The study presents a non-experimental type of research with a simple descriptive design; The general objective: explain the level of significant learning in the Initial Education teachers of the educational institutions “Los Arbolitos and 602 Primavera”. The instrument used was a questionnaire of questions about meaningful learning, with 24 items. The sample used in the research was 85 teachers from the two educational institutions in the district of Iquitos. The results of the study in general terms on the level of meaningful learning, of the 85 (100.0%) Initial teachers at the I.E. “Los Arbolitos and 602 Primavera, 29.4% (25) presented a low level, 42.4% (36) of them at the average level and 28.2% (24) of them presented a high level in learning. significant; It is concluded that significant learning in initial education teachers is above average.